Impact of distributed generation on voltage profile in radial feeder - Sarimuthu C.R.; Ramachandaramurthy V.K.; Mokhlis H.; Agileswari K.R. (Institute of Advanced Engineering and Science, 2023)
The use of distributed generation (DG) within distribution systems has increased for the last two decades due to worldwide increase in demand for electricity and governmental policy change from conventional energy to green energy. High levels of penetration of DG have many significant benefits but also come with many drawbacks such as voltage drop and power losses. This study presents the impact of DG at different locations in a distribution feeder in terms of the feeder voltage profile. A radial distribution system is simulated using PSCAD/EMTDC simulation software while changing the size and location of DG in the system. The obtained results are used for better understanding on the impact of DG on voltage profile in radial distribution feeder. 2017 Institute of Advanced Engineering and Science. All rights reserved.